New horizons at L’Anse aux Meadows - Ledger, Paul M. (Proc Natl Acad Sci U S A, 2019)
The UNESCO World Heritage site of L’Anse aux Meadows (LAM) in northern Newfoundland is the only undisputed site of pre-1492 presence of Europeans in the Americas. In August 2018, we undertook fieldwork at LAM to sample the peat bog 30 m east of the Norse ruins for a multiproxy paleoenvironmental assessment of Norse settlement. Instead, we encountered a new cultural horizon. Here we report our fieldwork at this iconic site and a Bayesian analysis of legacy radiocarbon data, which nuance previous conclusions and suggest Norse activity at LAM may have endured for a century. In light of these findings, we reflect on how the cultural horizon, containing nonnative ecofacts, may relate to indigenous or Norse activities.